An empirical analysis of the relationship between corporate governance and audit quality: Evidence from China - Xiao, Ying (2020)
This article examines the relationship between corporate governance characteristics (the board of directors, audit committees and ownership structure) and audit quality under the unique background of the Chinese securities market, and makes a contribution to the research of corporate governance and audit. In the view of the nature of ownership in the Chinese market, this article also compares the governance environment and audit quality of state-owned enterprises (SOEs) and non-state-owned enterprises (NSOEs). Based on the data of Chinese listed companies from 2006 to 2010, the empirical results show that board independence, board meetings, audit committees independence have a positive correlation with audit quality, while the audit committee size and SOEs have a negative relationship with audit quality. However, I did not find any significant correlation between other variables and audit quality. In accordance with many previous studies and agency theory, the results suggest that effective corporate governance may lead to higher audit quality, since effective corporate governance can improve internal control, maximize shareholder benefits, and supervise management’s behaviour.